2010
DOI: 10.1103/physrevlett.105.243003
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Energy Differences by BEC Interferometry on a Chip

Abstract: We investigate the use of a Bose-Einstein condensate trapped on an atom chip for making interferometric measurements of small energy differences. We measure and explain the noise in the energy difference of the split condensates, which derives from statistical noise in the number difference. We also consider systematic errors. A leading effect is the variation of the rf magnetic field in the trap with distance from the wires on the chip surface. This can produce energy differences that are comparable with thos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 43 publications
(38 reference statements)
2
58
0
1
Order By: Relevance
“…Nevertheless, some remarkable progress has been made using Bose-Einstein condensates (BECs) as resources [3,9,10]. For example, in the presence of attractive interactions these allow for the formation of bright soliton states, which are nondispersive and have been suggested as good candidates for the creation of macroscopic spatial superpositions [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, some remarkable progress has been made using Bose-Einstein condensates (BECs) as resources [3,9,10]. For example, in the presence of attractive interactions these allow for the formation of bright soliton states, which are nondispersive and have been suggested as good candidates for the creation of macroscopic spatial superpositions [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…A number of experiments have recently probed the physics of highly-elongated finite temperature Bose gases at equilibrium, including the direct observation and analysis of density [17,20,22] and phase fluctuations [23][24][25][26][27]. Understanding the properties of matter waves in such geometries is of key importance to atom interferometers [28][29][30][32][33][34][35][36] and atom chips [31,[37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a large number of experiments have been performed upon atomic Bose-Einstein condensates (BECs) trapped in double-well potentials (see, e.g., [1][2][3][4][5][6][7][8][9][10][11][12][13][14]). Each atom can be in a superposition of being in both wells, allowing for studies of macroscopic quantum coherence [1][2][3]5,[15][16][17][18] analogous to that found in a Josephson junction [4,8,13,[19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%